Wu-Mei-wan protects pancreatic β cells by inhibiting NLRP3 Inflammasome activation in diabetic mice - Xueping Yang; Fuer Lu; Lingli Li; Jingbin Li; Jinlong Luo; Siyi Zhang; Xinqiao Liu; Guang Chen (BMC, 2019)
Abstract Background Wu-Mei-Wan (WMW) is a traditional Chinese herbal formulation that is clinically prescribed to treat diabetes mellitus in China. WMW has been shown to alleviate damage in pancreatic β cells, but the underlying mechanism remains unclear. This study aims to explore how WMW plays a protective role in pancreatic islets. Methods Drug testing and mechanism analyses were performed on mice treated with three concentrations of WMW (4800, 9600, and 19,200 mg/kg/bw) for four consecutive weeks. Blood was collected from both db/db and wild-type mice to determine fasting blood glucose (FBG) and serum insulin levels. The expression of proteins related to apoptosis, cysteinyl aspartate-specific proteinase 12 (caspase-12) and B-cell leukemia 2 (Bcl-2), was measured by western blot. Interleukin-1β (IL-1β), interleukin-18 (IL-18), monocyte chemoattractant protein-1α (MCP-1α), and tumor necrosis factor-α (TNF-α) in the pancreas were tested with enzyme-linked immunosorbent assay (ELISA). Immunohistochemistry staining of F4/80 was performed to measure the pancreatic infiltration of macrophages. Western blot and immunofluorescence staining of the NLRP3 inflammasome were used to measure the expression of proteins related to apoptosis and inflammation. Results WMW dose-dependently reduced FBG and promoted serum insulin secretion in db/db mice compared to the wild-type controls. WMW protected pancreatic β cells with a pattern of decreasing caspase-12 and increasing Bcl-2 expression. WMW also reversed the upregulated production of IL-1β, IL-18, MCP-1α, and macrophage-specific surface glycoprotein F4/80 in diabetic mice. In addition, the protein expression levels of NLRP3 inflammasome components NLRP3, ASC, and caspase-1 (P20) were higher in db/db mice than in wild-type controls. Conclusions WMW inhibits the activation of the NLRP3 inflammasome to protect pancreatic β cells and prevent type 2 diabetes mellitus development.